Expansion of geographical indications to boost the development of brazilian cachaça (Research, Society and Development, 2021)
This study aimed to verify the relevance of the expansion of Geographical Indications (GI) as a way to boost the development of Brazilian cachaça. The method chosen for this research is qualitative in nature, through the use of bibliographic and document review techniques. The GI for cachaça in the form of Indication of Origin for the holders of the seal is of fundamental importance in the fight against counterfeits and identification for consumers as the true origin of the cachaças. the advantages of registering the enhancement of know-how and traditional techniques, adding value, notoriety, territorial development and preservation of culture, in addition to demonstrating that the product has qualities. Thus, it is concluded that the expansion of GI registrations of cachaça, will boost the development of cachaça and consequently the economic development for the country with the reduction of informality in the production and marketing of cachaça, which is a product of great relevance in soft Brazilian power.